A case of cribriform carcinoma of the skin: a newly described rare condition - Hyun Lee; Chong-Hyun Won; Chan-Sik Park (Korean Society of Pathologists & the Korean Society for Cytopathology, 2021)
Primary cribriform carcinoma of the skin is an indolent, rare, adnexal tumor. Although its malignant potential remains uncertain, no recurrence or metastasis has been reported. A 33-year-old man presented with a solitary, erythematous, subcutaneous nodule on the right knee. The clinical impression was epidermal cyst, and the resected tumor demonstrated a well-circumscribed mass in the dermis and subcutis. The tumor was composed of two regions: a solid component and a cribriform component. The solid component (90%) showed multiple solid nests of epithelial cells. Individual cells had large, oval-to-round, hyperchromatic, pleomorphic nuclei with a nuclear groove. The cribriform component (10%) showed similar neoplastic cells with many prominent lumina. Some lumina had an eosinophilic substance that exhibited a positive periodic acid-Schiff reaction. No recurrence or metastasis was observed within a follow-up period of eight months after excision. In conclusion, we report the first case of primary cribriform carcinoma of the skin in Korea.